Plan de mejoramiento con énfasis en ecommerce de la comercializadora de café: El placer. - Gaitán Gómez, Paula Andrea (Universidad Antonio Nariño, 2021)
The present investigation titled: "improvement plan with emphasis on e commerce of the coffee marketer: pleasure"; Its general purpose was to design a business improvement plan that will enable the financial expansion of the aforementioned marketer, located in the village of El Hatillo, in the municipality of Anzoátegui, Tolima. For this process, technological strategies typical of Ecommerce were articulated; the objective of the study was to identify the most effective alternatives for the implementation of online tools, designing a digital solution and implementing the operation of a web page aimed at making the coffee products produced by the marketer visible and commercializing.